211k views
2 votes
Solve using substitution
PLEASE HELP!

Solve using substitution PLEASE HELP!-example-1
User Joe Abrams
by
5.1k points

2 Answers

7 votes

Answer:

(2, 7, 2)

Explanation:

z=2, so we have:

x=2y-6z (this becomes x=2y-12)

-5x-2y=-24 (since there are no z's in this equation, we can't do anything.)

x-2y=-12

-5x-2y=-24

We can use the method of elimination to solve this system of equations, but first, to do that, we must multiply the top equation by -1

-x+2y=12

-5x-2y=-24

Now, the 2y and -2y can cancel out!

-6x=-12

x=2

If x=2, we can substitute that into this equation: x-2y=-12.

And we get: 2-2y=-12

Subtract 2: -2y=-14

y=7

Finally, we have our answer: x=2, y=7, z=2.

User Sefra
by
4.3k points
4 votes

Answer:

( 2, 7, 2 )

Explanation:

Take a look at the attachment below;

Solve using substitution PLEASE HELP!-example-1
User Chornbe
by
5.0k points